The development of simulation model on environmental uncertainty factors for interval project completion - Baharum, Zirawani; Rao Venkatesan, Yuvendra; Nabila Mohd Raidzuan, Syazwa; Imran Qureshi, Muhammad (International Journal of Engineering and Technology, 2018)
The construction industry has many underlying causes of uncertainty that has impact on late delivery of project completion’s performance as well as in time management. The issue on uncertainty delays directly impact the project performance that leads into unnecessary time extension. The objective of the research is the way to create a valid model towards the environmental uncertainty factors. Therefore, this research is conducted to identify the impact of environmental issues which affect the period of project completion using the Witness software system. A literature review revealed the types of other uncertainty factors that affect the project completion by using other softwareâ€™s such as Monte Carlo analysis and relative important index. This research is intended to measure the impact of each environmental factor using the Witness software system by evaluating their significant level of each. The significant level of the factors was determined by using the SPSS statistics software tools. The model will help to manage the time and costing factors by reducing the main impact from the environment. This will aid all project contractors in managing their resources and time utilities. Â